"Have You to This Point Assumed That I Am White?": Narrative Withholding since Playing in the Dark. (4th January 2019) - Ardoin, Paul
Abstract: This article traces a lineage of narrative experiments from Toni Morrison's Playing in the Dark: Whiteness and the Literary Imagination (1992) and "Recitatif" (1983) through recent texts by Colson Whitehead and Percival Everett. In her critical work, Morrison identifies a "sinister" tradition in which "the readers of virtually all of American fiction have been positioned as white." From that perspective, she argues, the characters in fiction can safely be presumed white, unless the narrative explicitly indicates otherwise; unless race is specifically addressed, the texts operate under a universal white default. Her short story challenges that default, in noteworthy and widely discussed fashion. This article attends to the strategy of narrative withholding in "Recitatif"—a strategy that illuminates and informs the brands of withholding at work in more recent works by Whitehead and Everett. Zone One (2014) and Glyph (1999) complicate Morrison's model, continuing her interrogation into narratives of race and the ways we narrate race. Where "Recitatif" foregrounds the role of race, though, the narrators of these two novels minimize it and purport to disregard it. The result is a brand of text that makes conspicuous the lack of narration of race, then the narration of race, and then the un -narration of race, utilizing a subversive set of strategies that may defamiliarize and refresh Morrison's critique for a new era.